Pengembangan Gim Edukasi “Smart Flowers” untuk Pengenalan Bunga Berbasis Android - Andrew Christian Thuwijaya; Yulia Ery Kurniawati (KALBISCIENTIA Jurnal Sains dan Teknologi, 2022)
This study aims to develop an interactive educational game for learning about flowers. This game is specifically for elementary school students due to their lack of knowledge and limited means to learn about flowers. The development of this game uses the Game Development Life Cycle method and Unity Engine software. The result of this study is an Android-based educational game, "Smart Flowers. It does not require an internet connection to play. The game's users can learn and expand their knowledge about the names, types and characteristics of flowers after using it. The alpha and user experience tests have been tested on the users. The results obtained from UX testing carried out by users on the "Smart Flowers" game application, this educational game can be used as an alternative media in learning flowers.